Wadah Seni Kolektif Senen - Samuel Axel Widjaya; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2020)
A 3rd place acts as an vital place in our daily life, aside from home as the 1st place or workplace as the 2nd place. 3rd place is a neutral public space, often seen as an alternative for some people. Everyone is welcome to visit and to do lots of activities on it. A 3rd place doesn’t have a fixed form, it can be anything the community around it needs it to be.Kawasan Senen was known as the centre of trade and art since forever. It can be seen from its history that became the birthplace of some of the finest artists in Indonesia. When Taman Ismail Marzuki was built on November 10th, 1968, the value of art in Kawasan Senen began to fade. But as time goes by, the value of art in Kawasan Senen begins to rise again. This event can be seen by the rise of art activities around Kawasan Senen such as Wayang Orang Bharata Purwa show that runs every Saturday, the free traditional dance classes that were held by Museum Kebangkitan Nasional and the emergence of Komunitas Planet Senen (KOPS) that actively trying to reintroduce the value of art to the Senen community. Senen Collective Art Space project was built on the hope to become the 3rd place to the community as well as providing and strengthening the value of Kawasan Senen. Keyword: Art in Senen; Collective Art; Neutral Public Space; Third Place AbstrakThe 3rd place merupakan tempat penting yang dibutuhan masyarakat, selain dari rumah sebagai the 1st place maupun tempat kerjanya sebagai 2nd place. 3rd place adalah ruang publik yang netral, sebagai tempat alternatif. Setiap orang dapat berkunjung dan melakukan berbagai aktivitas. Sebuah 3rd place dapat memiliki bentuk yang beragam, namun nyaman untuk beraktivitas sesuai dengan kehidupan dan budaya masyarakatnya. Kawasan Senen sejak dahulu dikenal sebagai pusat perdagangan dan kesenian yang cukup ramai. Hal ini dapat dilihat dari sejarah kawasannya yang menjadi tempat lahir beberapa seniman terkenal tanah air. Dibangunnya Taman Ismail Marzuki (TIM) pada 10 November 1968 membuat nilai seni di Kawasan Senen ini sempat luntur. Namun seiring waktu, nilai seni dari Kawasan Senen mulai kembali naik. Hal ini ditandai dengan beberapa aktivitas berunsur seni yang mulai dilaksanakan kembali di Kawasan ini seperti pertunjukan Wayang Orang Bharata Purwa yang rutin diadakan setiap hari Sabtu sampai kursus menari tradisional yang diadakan secara gratis oleh Museum Kebangkitan Nasional dan juga munculnya Komunitas Planet Senen (KOPS) yang kerap berusaha memperkenalkan unsur seni kepada masyarakat Senen. Proyek Wadah Seni Kolektif Senen ini bertujuan untuk menjadi wadah 3rd place bagi warga serta memfasilitasi dan memperkuat kembali unsur seni di Kawasan Senen ini.